(untitled) (Journal of Imam Al-Kadhim College, 2023)
The current research aims to (build a training program based on effective teaching skills for mathematics teachers and its impact on the acquisition of mathematical concepts for their students). To achieve the objectives of the research, the two null hypotheses were formulated as follows: 1) There is no statistically significant difference between the average scores of the students of the control group (the students of the teachers who did not undergo the training program) and the average scores of the students of the experimental group (the students of the mathematics teachers who underwent the training program) in the test of acquisition of mathematical concepts. 2)There is no statistically significant difference between the average scores of the students of the experimental group (students of mathematics teachers who underwent the training program) in the mathematics concepts acquisition test due to the gender variable. In light of this, a sample of mathematics teachers, numbering (30) male and female mathematics teachers in the General Directorate of Education in the third Karkh Governorate of Baghdad, and their students, numbering (3,450) male and female students, was selected to represent the (experimental sample), and a sample of mathematics teachers, numbering (30). A male and female teacher and their students, numbering (3730) male and female students, to represent the (control sample). Also, the training program and the research tool were built, represented by testing the students’ acquisition of mathematical concepts, as it consisted of (52) items, whose validity, reliability, and psychometric properties were confirmed, and after the results were quantified and treated statistically. The following became clear: 1)There is a statistically significant difference between the average scores of the students of the control group (the students of the teachers who did not undergo the training program) and the average scores of the students of the experimental group (the students of the mathematics teachers who underwent the training program) in the test of acquisition of mathematical concepts, in favor of the experimental group. 2) There is a statistically significant difference between the average scores of male and female students in the experimental group (students of mathematics teachers who underwent the training program) in the test of acquiring mathematical concepts, in favor of females. In light of the results, the researcher recommended the following: 1) The necessity of including effective teaching skills in educational programs for mathematics teachers. 2) Emphasis on the use of effective teaching skills in education in colleges of education and basic education. 3)Include a teacher’s guide to effective teaching skills for teaching mathematics.